ANALISIS KETERLAMBATAN PROSES PENYELESAIAN BUKA PASANG PROPELLER DAN REPLATING LAMBUNG KAPAL MT BLUE STARS DI PT. DOK DAN PERKAPALAN KODJA BAHARI GALANGAN III - Muhammad Raihan Desniansyah, (2022)
Ship repair is one of the interests and must be carried out on ships. Ship repair is the process of replacing ship parts that are no longer feasible and do not the minimum standards of seaworthiness from statutory and class regulations. The ship repair process begins with preparation, arrival meeting, docking and completion. At the preparation, surveyor owner reports the condition of the ship, then given recommendations from the Classification Bureau and a survey is carried out on the ship. For thestage, it arrival meeting is the preparation of a list of repairs and the preparation of a detailed work schedule. The docking stage is the stage where the ship begins to rise to the dock. After all stages are completed, then the solution is carried out. In the process of completion ship repairs often occur delays caused by several things, including work materials not ready, inadequate equipment, limited workers, inappropriate planning, inappropriate execution methods, additional work and so on. Management needed in a project and solutions are needed to avoid delays. Time is an important thing in the ship repair, it's because the schedule made must be appropriate to maximize the time that has been determined. A project that delayed can be caused by the owner ship, the shipyard or both parties. From the results that have been studied, delays tend to occur because of the owner ship, namely ordering materials ordered by the owner shipand adding work according to the recommendations of the owner ship. Delays in ship repair can be detrimental to both parties and the impact on both parties is also very large. So we need the right solution so that there is no delay in the next ship repair project.